Kaitan Antara Ruang Sobolev dan Ruang Lebesgue - Pipit Pratiwi Rahayu (Program Studi Matematika Fakultas Sains dan Teknologi UIN Sunan Kalijaga Yogyakarta, 2017)
Measureable function space and its norm with integral form has been known, one of which is Lebegsue Space and Sobolev Space. In applied Mathematics like in finding solution of partial differential equations, that two spaces is soo usefulness. Sobolev space is subset of Lebesgue space, its mean if we have a function that element of Sobolev Space then its element of Lebesgue space. But the converse of this condition is not applicable. In this research, we will give an example to shows that there is a function element of Lebesgue space but not element of Sobolev space